The Legal System of Disciplinary Authorities in Administrative Units - Dallaf, Mustafa Abdulhameed (Al-Mukhtar Journal of Social Sciences, 2018)
The legal system of disciplinary authorities in administrative units is considered crucial for achieving justice and effectiveness in the disciplinary process. The validity of disciplinary punishment requires it to be issued by authorized disciplinary authorities. The law stipulates that the legislator is solely responsible for establishing disciplinary authorities and determining their jurisdiction, and their jurisdiction cannot be diminished unless there is explicit legal authorization. The judge is allowed to deem the punishment invalid if it involves a lack of competence, and the judicial decision in this regard is immediately enforceable. Disciplinary authorities are not allowed to delegate or modify jurisdictional rules unless there is explicit legal authorization. The Libyan legal system follows three methods of discipline, namely administrative, judicial, and semi-judicial methods, each having its advantages and disadvantages. Judicial entities play a role in disciplining employees through disciplinary trials, and this method provides judicial guarantees for employees, although it can be slow at times. On the other hand, disciplinary boards are responsible for holding employees accountable before a body that includes administrative and judicial elements, and these boards are administrative entities with judicial expertise. The legal system must be committed to providing powers and guarantees to employees in the disciplinary process to ensure justice and effectiveness in this system.